An efficient full-wavefield computational approach for seismic testing in a layered half-space. Issue 161 (October 2022) - Lin, Chih-Ping; Wu, Tsai-Jung; Pan, Ernian
Abstract: Inversion of subsurface shear-wave velocity profile based on effective dispersion curve or full wavefield is still rare due to the lack of efficient forward computation kernel for the full wavefield in a layered medium. To facilitate exploiting the complete signal content in seismic testing, an efficient new computational framework for modeling synthetic full wavefields in horizontally layered systems is proposed. Dynamic response of an isotropic elastic layered system subjected to vertical loading is implemented and thoroughly validated. The new procedure is based the Fourier-Bessel series expansion (not the traditional Fourier-Bessel transform), and it is at least two-orders faster than the current full wavefield computation method based on integral transformation. It considers survey parameters and models all wave phenomena, including near-field effect and leaky waves, which cannot be captured by the modal summation method. Examples of full wavefield simulation are presented to demonstrate different levels of information provided by the experimentally available fundamental mode, broadband effective dispersion curve, and the full velocity spectrum. Different earth models may have similar fundamental modes or even effective dispersion curves; however, their difference manifests in different higher-mode contributions and can only be exploited by utilizing the entire velocity spectra including the vertical and radial components. The coupling between the vertical and radial components in terms of their spectral ratio and phase difference can provide additional constraints (data) in seismic testing. Highlights: Loading within a circle, instead of a point force, is used for better mimicking the surface testing load. The computationally efficient finite Fourier-Bessel summation, instead of Hankel integral, is proposed. Solution for vertical load using the stiffness matrix is presented, which can be easily extended to other loading conditions. The full-wavefield solution reveals the important effects of near field, leaky and lateral waves, and radial-to-vertical characteristics.